STRUCTURAL ANALYSIS OF THE MYPES END PYMES - Herrera García, Beatriz (2011)
The size of informality in Peru is 38.1 percent of GDP, much of that informality is relevant to micro and small companies, nationwide they are largely concentrated in extractive industries (agriculture and fisheries). However, according to studies, it is in those sectors where there are fewer formal businesses.